Nanographene–Osmapentalyne Complexes as a Cathode Interlayer in Organic Solar Cells Enhance Efficiency over 18%. Issue 30 (12th June 2021) - Liu, Longzhu; Chen, Shiyan; Qu, Yangyang; Gao, Xiang; Han, Liang; Lin, Zhiwei; Yang, Liulin; Wang, Wei; Zheng, Nan; Liang, Yongye; Tan, Yuanzhi; Xia, Haiping; et al.
Abstract: Interface engineering is a critical method by which to efficiently enhance the photovoltaic performance of nonfullerene solar cells (NFSC). Herein, a series of metal–nanographene‐containing large transition metal involving dπ – pπ conjugated systems by way of the addition reactions of osmapentalynes and p ‐diethynyl‐hexabenzocoronenes is reported. Conjugated extensions are engineered to optimize the π‐conjugation of these metal–nanographene molecules, which serve as alcohol‐soluble cathode interlayer (CIL) materials. Upon extension of the π‐conjugation, the power conversion efficiency (PCE) of PM6:BTP‐eC9‐based NFSCs increases from 16% to over 18%, giving the highest recorded PCE. It is deduced by X‐ray crystallographic analysis, interfacial contact methods, morphology characterization, and carrier dynamics that modification of hexabenzocoronenes‐styryl can effectively improve the short‐circuit current density ( J sc ) and fill factor of organic solar cells (OSCs), mainly due to the strong and ordered charge transfer, more matching energy level alignments, better interfacial contacts between the active layer and the electrodes, and regulated morphology. Consequently, the carrier transport is largely facilitated, and the carrier recombination is simultaneously impeded. These new CIL materials are broadly able to enhance the photovoltaic properties of OSCs in other systems, which provides a promising potential to serve as CILs for higher‐quality OSCs. Abstract : Newly synthesized hexabenzocoronene (HBC)–osmapentalyne complexes that combine fragments of graphene and metalla‐aromatics are emerging as cathode interlayer materials. Further extending the dπ – pπ conjugated systems of osmapentalynes, the most successful complex, in this work, HBC‐S is found to boost the efficiency of non‐fullerene solar cells to over 18%.